The characterisation of AOP2: a gene associated with the biosynthesis of aliphatic alkenyl glucosinolates in Arabidopsis thaliana - Neal, Calida S (BioMed Central, 2010)
BACKGROUND: Glucosinolates, a group of nitrogen and sulfur containing compounds associated with plant-insect interactions, are produced by a number of important Brassicaceae crop species. In Arabidopsis the AOP2 gene plays a role in the secondary modification of aliphatic (methionine-derived) glucosinolates, namely the conversion of methylsulfinylalkyl glucosinolates to form alkenyl glucosinolates, and also influences aliphatic glucosinolate accumulation. RESULTS: This study characterises the primary structural variation in the coding sequences of the AOP2 gene and identifies three different AOP2 alleles based on polymorphisms in exon two. To help determine the regulatory mechanisms mediating AOP2 expression amongst accessions, AOP2 5' regulatory regions were also examined however no major differences were identified. Expression of the AOP2 gene was found to be most abundant in leaf and stem tissue and was also found to be light dependent, with a number of light regulatory elements identified in the promoter region of the gene. In addition, a study was undertaken to demonstrate that the Arabidopsis AOP2 gene product is functional in planta. The over-expression of a functional AOP2 allele was found to successfully convert the precursor methylsulfinyl alkyl glucosinolate into the alkenyl form. CONCLUSIONS: The expression of the AOP2 gene has been found to be influenced by light and is most highly expressed in the photosynthetic parts of the Arabidopsis plant. The level of AOP2 transcript decreases rapidly in the absence of light. AOP2 exists as at least three alleles in different Arabidopsis accessions and we have demonstrated that one of these, AOP2-2, is functionally able to convert methylsulfinyl glucosinolates into the alkenyl form. The demonstration of the in planta functionality of the Arabisopsis AOP2 gene is an important step in determining the feasibility of engineering glucosinolate profiles in food plants.